Divalent EuRh2Si2 as a reference for the Luttinger theorem and antiferromagnetism in trivalent heavy-fermion YbRh2Si2 - M. Güttler (Nature Portfolio, 2019)
Heavy-fermion materials have unusual electronic behavior due to a dual localized-itinerant character of 4f electrons. Here, by studying divalent EuRh2Si2, the authors gain insight into the electronic states of the trivalent heavy fermion system YbRh2Si2 and show that it experimentally demonstrates Luttinger’s theorem.